2016
DOI: 10.2340/16501977-2133
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted locomotor training enhances ankle performance in adults with incomplete spinal cord injury

Abstract: These findings provide evidence that robotic-assisted locomotor training improves ankle joint control, which may translate into enhanced walking performance in individuals with chronic incomplete spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As evidence, beneficial adaptations to spinal neuronal pathways have been observed in response to ABPT by probing soleus Hoffmann reflex during walking in which homosynaptic facilitation normalized, homosynaptic depression reversed, and presynaptic inhibition of Ia afferents improved [ 83 , 85 , 86 ]. The functional recovery in persons with incomplete SCI undergoing ABPT has also been associated with findings that indicate greater descending corticospinal drive, including increased ankle dorsiflexor and knee extensor maximal motor-evoked potentials, a probe of corticospinal tract excitability [ 87 ], and improved ankle dorsiflexor and plantar flexor muscle co-activation patterns during walking [ 88 ]. Possible mechanisms underlying ABPT-mediated neuroplasticity may involve the upregulation of brain-derived neurotrophic factor and/or its receptor, tyrosine kinase B mRNA, in the spinal cord, which mediate improvements of synaptic transmission, axon regeneration, and motor neuron survival [ 89 ].…”
Section: Activity-based Physical Therapy (Abpt) After Scimentioning
confidence: 99%
“…As evidence, beneficial adaptations to spinal neuronal pathways have been observed in response to ABPT by probing soleus Hoffmann reflex during walking in which homosynaptic facilitation normalized, homosynaptic depression reversed, and presynaptic inhibition of Ia afferents improved [ 83 , 85 , 86 ]. The functional recovery in persons with incomplete SCI undergoing ABPT has also been associated with findings that indicate greater descending corticospinal drive, including increased ankle dorsiflexor and knee extensor maximal motor-evoked potentials, a probe of corticospinal tract excitability [ 87 ], and improved ankle dorsiflexor and plantar flexor muscle co-activation patterns during walking [ 88 ]. Possible mechanisms underlying ABPT-mediated neuroplasticity may involve the upregulation of brain-derived neurotrophic factor and/or its receptor, tyrosine kinase B mRNA, in the spinal cord, which mediate improvements of synaptic transmission, axon regeneration, and motor neuron survival [ 89 ].…”
Section: Activity-based Physical Therapy (Abpt) After Scimentioning
confidence: 99%
“…Through intense repetitive practice, it is postulated that ABTs activate sublesional spinal networks that promote beneficial neuromuscular adaptations by retraining the CNS to recover task-specific motor activities, via stimulation of the central pattern generator (CPG) in the lumbosacral region of the spinal cord [ 166 ]. Indeed, a number of studies involving persons with motor-incomplete SCI indicate that BWSTT produces several functional benefits, including (1) improved temporal gait parameters associated with walking ability (e.g., increased number of steps, faster cadence, and improved muscle activation patterns) [ 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ]; (2) improved muscle strength and rate of torque development in impaired limbs, and reduced detrimental co-activation of antagonist muscle groups [ 24 , 169 , 171 , 178 , 179 , 180 ]; and (3) reduced muscle atrophy [ 24 , 178 , 181 , 182 , 183 , 184 ] ( Table 1 ). However, when data from well-controlled randomized clinical trials assessing BWSTT after SCI [ 179 , 185 , 186 , 187 , 188 ] are pooled, there appears to be only limited meaningful improvement in overground walking speed or distance [ 4 , 189 , 190 , 191 ], given that the minimal clinically important difference in walking speed is reported as 0.13 m/s in the SCI population [ 192 ].…”
Section: Activity-based Physical Rehabilitation After Scimentioning
confidence: 99%
“…Likewise, Jayaraman et al reported that nine-weeks of BWSTT enhanced knee extensor and ankle plantar flexion voluntary muscle activation and increased plantar flexion peak torque by 43%, which accompanied a 15% increase in plantar flexor CSA [ 201 ], an important finding given that lower extremity strength is positively associated with walking function after SCI [ 42 ]. However, others have reported much less robust strength improvements [ 202 , 203 ] or no strength improvement [ 171 ] in response to BWSTT.…”
Section: Activity-based Physical Rehabilitation After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Both older (2,3) and more recent studies (4)(5)(6)(7)(8) have reported encouraging results. Locomotor gait training increased muscle volume (7), improved activation of muscles in the lower limbs (9), increased ankle stability (10), and was associated with decreased spasticity (11). There is also some evidence that BWSLT improves subjects' wellbeing and quality of life (6), and the benefits seem to be sustained (12).…”
mentioning
confidence: 99%